INSULATION IMPOSSIBLE: MONETARY POLICY AND REGIONAL DEBT SPILLOVERS IN A FEDERATION. Issue 2 (28th January 2014) - Cooper, Russell; Kempf, Hubert; Peled, Dan
Abstract This paper studies the effects of monetary policy in the presence of debt spillovers within a monetary union. When capital markets are integrated, the fiscal policy of any member country will generally influence equilibrium wages and interest rates across the whole union. We ask whether there exists a monetary policy which can offset these spillovers. Within a general class of monetary policy rules, there does not exist one that completely insulates agents in one region from fiscal policy in the other. These debt spillovers will affect welfare through two channels: intertemporal efficiency and redistribution.